2010
DOI: 10.3113/fai.2010.0815
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Explosive Muscle Strength and Medial Longitudinal Arch of the Foot

Abstract: This data may be useful in evaluating patients with painful flat feet and any strength deficits they may have.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
1
11
1
2
Order By: Relevance
“…The results of our study differ from the results of those by Lizis, Posadzki & Smith (2010), which indicate the absence of statistically signifi cant differences in the manifestation of explosive strength of legs comparing to the postural status of longitudinal foot arch in both male and female respondents. The results do not match the research by Aleksandrovic & Kottaras (2015) either, in which there was no statistically signifi cant difference in the manifestation of explosive strength of lower extremities in relation to the postural foot status.…”
Section: Konfl Ikt Interesa MI Izjavljujemo Da Nemamo Konfl Ikt Interesacontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of our study differ from the results of those by Lizis, Posadzki & Smith (2010), which indicate the absence of statistically signifi cant differences in the manifestation of explosive strength of legs comparing to the postural status of longitudinal foot arch in both male and female respondents. The results do not match the research by Aleksandrovic & Kottaras (2015) either, in which there was no statistically signifi cant difference in the manifestation of explosive strength of lower extremities in relation to the postural foot status.…”
Section: Konfl Ikt Interesa MI Izjavljujemo Da Nemamo Konfl Ikt Interesacontrasting
confidence: 99%
“…Rezultati našeg istraživanja razlikuju se od rezultata istraživanja Lizisa. Posadzkog i Smita (Lizis, Posadzki & Smith, 2010), koji ukazuju na nepostojanje statistički značajne razlike u ispoljavanju eksplozivne snage nogu u odnosu na posturalni status longitudinalnog svoda stopala kod ispitanika oba pola. Takođe, rezultati se ne podudaraju ni sa istraživanjem Aleksandrovića i Kotarasa (2015), u kojem nije utvrđena statistički značajna razlika u ispoljavanju eksplozivne snage donjih ekstremiteta u odnosu na posturalni status stopala.…”
Section: Dicussion and Conclusionunclassified
“…The study of the footprint was obtained by a pedograph. Three measurements were used: Clarke's angle, the Chippaux-Smirak index, and the Staheli arch index [6][7][8].…”
Section: Flat Foot Diagnosticmentioning
confidence: 99%
“…Footprint analysis using a pedograph is a simple, swift, and cost-effective method. The three measurements habitually used in the diagnosis of flat foot using a pedograph are: Clarke's angle [6] the Chippaux-Smirak index [7] and the Staheli index [8].…”
Section: Introductionmentioning
confidence: 99%
“…This problem proves that the index for identifying function of foot has not tried or tested yet. In adults, however, there is no proven relation between a person's shape, such as the height of the foot arch, and physical function performance, such as the power of the lower limb muscles [9]. Equally, in elementary school students, Morita et al showed that the height of the foot arch is irrelevant to TGS and to performance involving lower limbs, but that TGS does have a bearing on performance involving lower limbs [10].…”
mentioning
confidence: 99%